ANALISIS KINERJA PERUSAHAAN BERDASARKAN VARIABEL DIVERSIFIKASI BISNIS DAN SEKTOR INDUSTRI - Sutisna Sutisna (LP2M Universitas Bina Bangsa, 2022)
This study intends to determine how the effect of horizontal diversification, vertical diversification and conglomeration diversification on company performance. In addition, this study also wants to know whether the type of industry affects the company's performance. This research method is a quantitative research. The population in this study were all companies listed on the Indonesia Stock Exchange (IDX) from 2015-2019. The number of samples is 44 companies with 220 observations. The method of analysis used is multiple linear regression. The results showed that vertical diversification within the company had a significant negative effect on company performance. The more a company diversifies vertically, the smaller the ROA or performance that the company gets. In addition, horizontal diversification also has a significant negative effect on company performance. While the type of manufacturing industry has a significant positive effect on company performance. There is no effect of the type of service industry on the company's performance and the type of property industry also has no effect on the company's performance